Assessment of the COVID-19 related knowledge and its association with perceived worries of COVID-19 infection and severe illness among higher education students in 26 countries: A cross-sectional study. (20th October 2021) - Berhe, N; Van De Velde, S; Van Hal, G
Abstract: Background: During COVID-19, various public health measures such as physical distancing and distance learning are being implemented. As a consequence, higher education (HE) students face social as well as mental trauma at a crucial developmental stage in their lives. Having inadequate COVID-19 related knowledge can lead to an exaggerated worrying as well as to negative COVID-19 outcomes. Our study aims to assess COVID-19 related knowledge and its association with perceived worries among HE students. Methods: Between April 27 & July 7, 2020, a cross sectional survey, called COVID-19 International Students Well-being Study (C19 ISWS) was conducted in HE institutions in 26 countries. A stratified convenience sampling technique was used to select HE institutions. An online questionnaire was distributed to HE students to investigate behaviour and mental well-being. Descriptive, bivariate and mixed effect logistic regression analysis were conducted using R software. Perceived worries of COVID-19 infection as well as of severe COVID-19 illness (outcome measures) were studied. Results: Over 127, 000 students from more than 100 HE institutions in 26 countries filled out the questionnaire. 97, 495 (76.5%) respondents have never acquired COVID-19 (our study population). 70, 365 (72.1%) of these respondents were female. The most frequent correct response to COVID-19 related knowledge questions among respondents was observed about having the virus without having symptoms (94.3%). The odds of being worried of contracting severe COVID-19 illness among respondents with poor knowledge is 1.15 (95%CI:1.11, 1.18). Conclusions: COVID related knowledge was independently associated with perceived worries of contracting severe COVID-19 illness. We recommend scaling up of awareness creation campaigns to increase the comprehensive and timely COVID-19 related knowledge in order to tackle exaggerated perceived worries of severe COVID-19 illness among HE students.